Concussion Reporting and Safeguarding Policy Development in British American Football: An Essential Agenda - Travis, Eleanor; Thornton, Claire; Scott-Bell, Andrea (Frontiers in Sports and Active Living, 2021)
The objective of this study was to examine concussion reporting and safeguarding policy in British American Football (BAF). Data were collected via an online survey tool. The data presented are part of a broader study that examined the injury profiles, reporting concussion behaviours and medical provision in BAF. When asked about overall playing experience, concussion like symptoms were found in over half (58.8%) of participants. Of those, 36.4% reported they had previously been formally diagnosed with a concussion whilst playing BAF. Just under half of participants (44.7%) had suspected they’d had a concussion, although this was not formally diagnosed, and 23.5% of participants had previously hidden concussion symptoms. Fifty eight percent of teams reported they did not have a regular game day medic, with a range of hired medical personnel who attended games. Prominent barriers to consistent medical hire included; budget, institutional barriers, lack of medic reliability and game knowledge. BAF is a developing sport with a clear vision for growth of participation. Yet, the current concussion and medical provision policy do not address the sport’s welfare needs. Through discussion of these policies in the context of this study’s findings, we highlight vital areas for concern in policy and practice that the British American Football Association need to address in their medical and concussion policies.